Is theology a science? : the nature of the scientific enterprise in the scientific theology of Thomas Forsyth Torrance and the anarchic epistemology of Paul Feyerabend - Munchin, David (Studies in systematic theology (Leiden, Netherlands) ;, 2011)
This book analyses whether the scientific epistemology of Torrance's Theological Science project is robust enough to withstand the anarchic and distinctively post-modern challenge of Paul Feyerabend: 'The worst enemy of science'.